Blockade of CD40L inhibits immunogenic maturation of lung dendritic cells: Implications for the role of lung iNKT cells in mouse models of asthma. (May 2020) - Deng, Nishan; Chen, Qianhui; Guo, Xuxue; Liu, Linlin; Chen, Shuo; Wang, Ailing; Li, Ruiyun; Huang, Yi; Ding, Xuhong; Yu, Hongying; Hu, Suping; Zhao, Yang; et al.
Highlights: Allergic asthma is driven by T helper type 2 (Th2) cell responses. Lung dendritic cells (LDCs) are critical in initiating Th2 cell responses. CD40 ligation is important for LDCs to activation in allergic asthma. iNKT cells upregulate CD40 ligand (CD40 L) upon stimulation in allergic asthma. Blockade of CD40 L expressed in lung iNKT cells suppresses maturation of LDCs. Abstract: Some studies have shown that maturation of dendritic cells (DCs) is modulated directly by pathogen components via pattern recognition receptors such as Toll-like receptors, but also by signal like CD40 ligand (CD40 L or CD154) mediated by activated T cells. Several reports indicate that invariant natural killer T (iNKT) cells up-regulate CD40 L upon stimulation and thereby induce activation and maturation of DCs through crosslink with CD40. Our previous findings indicated that iNKT cells promote Th2 cell responses through the induction of immunogenic maturation of lung DCs (LDCs) in the asthmatic murine, but its mechanism remains unclear. Therefore, we investigated the immunomodulatory effects of blockade of CD40 L using anti-CD40 L treatment on Th2 cell responses and immunogenic maturation of LDCs, and further analyzed whether these influences of blockade of CD40 L were related to lung iNKT cells using iNKT cell-deficient mice and the combination treatment of specific iNKT cell activation with anti-CD40 L treatment in murine models of asthma. Our findings showed that blockade of CD40 L using anti-CD40 L treatment attenuated Th2 cell responses in wild-type (WT) mice, but not in CD1d-deficient mice sensitized and challenged with ovalbumin (OVA) or house dust mite (HDM). Meanwhile, blockade of CD40 L down-regulated immunogenic maturation of LDCs in WT mice, but not in CD1d-deficient mice sensitized and challenged with OVA. Additionally, agonistic anti-CD40 treatment reversed the inhibitory effects of anti-CD40 L treatment on Th2 cell responses and LDC activation in an OVA-induced mouse model of asthma. Furthermore, LDCs from asthmatic mice treated with anti-CD40 L could significantly reduce the influence on Th2 cell responses in vivo and in vitro . Finally, α-Galactosylceramide plus anti-CD40 L treatment stimulated lung iNKT cells, but suppressed Th2 cell responses in the asthmatic mice. Taken together, our data raise an evidence that blockade of CD40 L attenuates Th2 cell responses through the inhibition of immunogenic maturation of LDCs, which may be at least partially related to lung iNKT cells in murine models of asthma.